Human computer interaction - Ali Selamat; Md Hafiz Selamat; Nor Azman Ismail (Penerbit UTM Press, 2014)
This book serves as an introduction to computer science at the undergraduate level. It provides a detailed overview of the state-of-the-art concepts in human computer interaction (HCI)